Surveying Mutagenic and Anti-mutagenic Effects of Citrus Limon - Entezari, Malihe; Majd, Ahmad; Falahian, Fathollah; Mehrabian, Sedighe; Hashemi, Mehrdad; Movafagh, Abolfazl (Asian Pacific Journal of Cancer Biology, 2017)
Background and objective: Cancer is one of the main causes of mortality in the world and countless mutagenic chemical compound kill millions of cancer patients every year. Scientists are searching for natural foodstuff to prevent cancer. The present paper examines anti-mutagenic and anti-carcinogenic effects of citrus lemon. Methodology: Human astrocytoma cancerous cell line was cultured in DMEM (Gibco) with FBS10% (fetal bovine serum), L-glutamine, penicillin, and streptomycin at 37ºC for two days. Then the samples were treated with citrus lemon juice and biotic potential of cells was examined through the MTT method. Anti-mutagenic and anti-carcinogenic effects of citrus lemon were studied through back mutation assessment standard method (Ames test). The test was done using Salmonella typhimurium strain (TA100) with the mutation in histidine operon that needs external histidine source. The strain creates the reverse colony in presence of carcinogenic agents (sodium azide). Findings: Based on the MTT method, human astrocytoma cancerous cell line demonstrated significant cellular death compared with the control groups (p<0.01). Ames test showed that the juice prevented back mutation and rate of inhibition, based on the anti-mutagenic effect, of half-ripen and ripen citrus lemon was 71.7% and 34.3% respectively. In addition, the anti-carcinogenic effect of half-ripen and ripen citrus lemon were 83.3% and 50% respectively. Conclusion: Anti-mutagenic and anti-carcinogenic effects of citrus lemon were examined for the first time. The results showed that in this regard half-ripen citrus lemon was more effective than ripening citrus lemon.